Relación entre los síntomas de los trastornos de conducta alimentaria y la autoestima en escolares y universitarios - Bocian Otero, Camila Maria (2022)
The present study sought to identify the relationship between self-esteem and eating disorder symptoms in school and university students. The Institute for Health Metrics and Evaluation (IHME, 2020) states that in 2019, 0.11% of the world population with diseases, under the age of twenty, suffers from some type of eating disorder. A review was carried out in five databases, identifying inclusion and exclusion criteria, from which 7 articles were extracted for further analysis. It was found that all studies report significant bivariate correlations between self-esteem and eating disorder symptoms. The discussion was carried out around the main findings, such as the relationship with other significant variables such as perfectionism, internalization of the social ideal of the body and depression. It can be concluded that there is a negative bivariate correlation between self-esteem and eating disorder symptoms; it can also be pointed out that self-esteem works as a predictive and statistically significant variable in relation to the symptoms of eating disorders, as long as it is accompanied by other factors that better explain the variance